PENGEMBANGAN SISTEM AUDIT REKAM MEDIS BERBASIS WEB UNTUK EVALUASI KUALITAS DATA - Faik Agiwahyuanto; Fitria Wulandari; Suyoko; Maulana Tomy Abiyasa (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2026)
The low quality of Electronic Medical Record (EMR) data can become a significant barrier in the insurance claim process, particularly within hospital settings. The problem identified at RS Pantiwilasa Citarum Semarang is caused by incomplete EMR data in the hospital information system used as the basis for insurance claim submissions. This incompleteness has the potential to cause substantial financial losses for the healthcare institution. The issue mainly stems from the lack of attention given by physicians in completing supporting medical data documents accurately and comprehensively. This study aims to provide a significant contribution by developing a quantitative and qualitative audit system designed to comprehensively evaluate EMR data quality. The research method combines several approaches, including system development methods, quantitative testing, and qualitative evaluation. The study applies the Software Development Life Cycle (SDLC) method to develop a web-based audit system covering requirements analysis, system design, system implementation, and system testing. The result of this study is SIMAURA (Medical Record Audit System Application), a website-based application currently being developed in the medical record laboratory of the Diploma-III Medical Record and Health Information program.